2018
DOI: 10.1093/cercor/bhy115
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Anatomical Connectivity Patterns Differentiate Subdivisions of the Nonlemniscal Auditory Thalamus in Mice

Abstract: Systematic examination of the inputs and outputs of the nonlemniscal auditory thalamus will facilitate the functional elucidation of this complex structure in the central auditory system. In mice, comprehensive tracing studies that reveal the long-range connectivity of the nonlemniscal auditory thalamus are lacking. To this end, we used Cre-inducible anterograde and monosynaptic retrograde viruses in Calbindin-2A-dgCre-D and Calretinin-IRES-Cre mice, focusing on the differences across subdivisions of the nonle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 91 publications
4
41
1
Order By: Relevance
“…We found that TeA/Ect received clear projections from the auditory thalamus, and almost all the CTB-555-positive neurons were located within MGd. This finding is interesting because TeA/Ect is located outside the auditory cortex; however, it is consistent with Cai et al (2018) . Next, we injected CTB-555 into the ventrocaudal corner of the auditory cortex ( Supplementary Fig.…”
Section: Resultssupporting
confidence: 56%
“…We found that TeA/Ect received clear projections from the auditory thalamus, and almost all the CTB-555-positive neurons were located within MGd. This finding is interesting because TeA/Ect is located outside the auditory cortex; however, it is consistent with Cai et al (2018) . Next, we injected CTB-555 into the ventrocaudal corner of the auditory cortex ( Supplementary Fig.…”
Section: Resultssupporting
confidence: 56%
“…In addition, we also found that the excitatory Vglut2+ neurons and inhibitory Gad2+ neurons in the PC share approximately similar proportions of whole-brain inputs from most input sources of them. This is similar to many tracing results from other brain areas that different types of neurons within a certain brain area share similar input patterns across the whole brain (Zhang et al, 2017;Ährlund-Richter et al, 2019;Cai et al, 2019). While it should be noted that, different types of PC neurons may be distinct in their cell morphology, layer distributions, neural circuits and neural response characteristics Bekkers, 2006, 2011;Diodato et al, 2016;Large et al, 2016).…”
Section: Cell-type-specific Inputs To the Pcsupporting
confidence: 84%
“…L6 CTs are the largest component of the corticofugal projection system and one of the largest classes of projection neurons in the brain, but their contribution to brain function and behavior remain an unsolved mystery. In the auditory cortex (ACtx), L6 CT axons bifurcate into a subcortical branch that deposits axon collaterals onto GABAergic neurons in the thalamic reticular nucleus en route to the medial geniculate body (MGB) and a vertically oriented intracortical branch that collateralizes extensively within the local vertical column, predominantly synapsing onto neurons in layers 5a and 6 (Cai et al, 2018;Guo et al, 2017;Llano and Sherman, 2008;Prieto and Winer, 1999;Winer et al, 2001) ( Fig. 1A).…”
Section: Main Textmentioning
confidence: 99%